Planning for the Implementation of Strengthening Religious Moderation in PAI Learning to Shape Student Character in MIN 3 and MIN 13 East Aceh - Fuad, Phil Zainul; Alfarabi, Muhammad; Khalidi, Nasrun (Budapest International Research and Critics University, 2022)
The aims of this study are to find out planning for the implementation of strengthening religious moderation in PAI learning to shape student character in MIN 3 and MIN 13 east aceh. This study used that qualitative research method. The result of this study shows that Planning for the implementation of strengthening religious moderation in PAI learning in MIN 3 and MIN 13 East Aceh is carried out by increasing the ability of teachers to master the strengthening of religious moderation, procuring PAI learning books in accordance with KMA 183, providing guidance and supervision to PAI teachers in preparing lesson plans.